Metallic glass powder, additively fabricated bodies, and electronic devices

JP2026142613APending Publication Date: 2026-09-08SEIKO EPSON CORP

Patent Information

Application Number
JP2025029681
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2026-09-08

Smart Images

  • Figure 2026142613000001_ABST
    Figure 2026142613000001_ABST
Patent Text Reader

Abstract

To provide a metallic glass powder capable of producing additively manufactured bodies with high hardness and corrosion resistance, and that are non-magnetic; an additively manufactured body produced using such metallic glass powder; and an electronic device equipped with such an additively manufactured body. [Solution] A metallic glass powder used in powder bed fusion additive manufacturing, characterized in that the Cr content is 10.0 atomic% or more and 20.0 atomic% or less, the Mo content is 10.0 atomic% or more and 20.0 atomic% or less, the C content is 10.0 atomic% or more and 20.0 atomic% or less, the B content is 5.0 atomic% or more and 15.0 atomic% or less, the P content is 0.001 atomic% or more and 0.500 atomic% or less, the remainder being Fe and impurities, having an amorphous structure, and the difference between the crystallization temperature Tx and the glass transition temperature Tg is 50°C or more and 80°C or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to metallic glass powder, additively fabricated bodies, and electronic devices. [Background technology]

[0002] Patent Document 1 discloses a method for obtaining a three-dimensional object by repeatedly performing the following steps: spreading out a metal powder with SUS304 as the framework metal and Sn as the coating metal to form a powder layer, and irradiating the powder layer with laser light to melt it and form a joint. According to such a method for creating three-dimensional objects, it is possible to manufacture objects with high mechanical strength. [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2002-249804 [Overview of the project] [Problems that the invention aims to solve]

[0004] The metal powder described in Patent Document 1 uses SUS304 as the skeletal metal. Therefore, there is a problem in that the hardness of the manufactured molded object is insufficient. When the hardness of the molded object is low, the exterior parts made from the molded object are easily scratched. [Means for solving the problem]

[0005] The metallic glass powders used in the application examples of the present invention are A metallic glass powder used in powder bed fusion additive manufacturing, The Cr content is between 10.0 atomic% and 20.0 atomic%. The Mo content is between 10.0 atomic% and 20.0 atomic%. The C content is between 10.0 atomic% and 20.0 atomic%. The content of B is 5.0 atomic% or more and 15.0 atomic% or less. The P content is between 0.001 atomic% and 0.500 atomic%. The remainder consists of Fe and impurities. It has an amorphous structure, The difference between the crystallization temperature Tx and the glass transition temperature Tg is between 50°C and 80°C.

[0006] The additively fabricated body according to an example of the application of the present invention is The metallic glass powder according to an application example of the present invention is subjected to additive manufacturing using a powder bed fusion method.

[0007] The electronic device according to an example of the application of the present invention is The present invention comprises an additively manufactured body according to an example of its application. [Brief explanation of the drawing]

[0008] [Figure 1] This is an example of a DSC curve obtained for the metallic glass powder according to the embodiment. [Figure 2] Table 1 shows the composition of the metallic glass powder. [Figure 3] Table 2 shows the composition of the metallic glass powder or metal powder. [Figure 4] Table 3 shows the properties of metallic glass powder and the evaluation results of the additively fabricated bodies. [Figure 5] Table 4 shows the properties of metallic glass powder or metallic powder and the evaluation results of the additively manufactured bodies. [Modes for carrying out the invention]

[0009] Hereinafter, the metallic glass powder, additively fabricated body, and electronic device according to the present invention will be described in detail based on the embodiments shown in the accompanying drawings.

[0010] 1. Metallic glass powder The metallic glass powder according to this embodiment is a raw material powder used in additive manufacturing using the powder bed fusion method.

[0011] The powder bed fusion additive manufacturing method is a method for obtaining a three-dimensionally additively manufactured body by repeating the operations of forming a layer of raw material powder (a powder bed), melting and welding positions corresponding to a cross-section of the additively manufactured body to be formed with a heat source, and further forming another layer of raw material powder thereon. Electromagnetic radiation is preferably used as the heat source, and laser beams or electron beams are more preferably used.

[0012] The metallic glass powder according to the embodiment has a Cr content of 10.0 atomic % or more and 20.0 atomic % or less, a Mo content of 10.0 atomic % or more and 20.0 atomic % or less, a C content of 10.0 atomic % or more and 20.0 atomic % or less, a B content of 5.0 atomic % or more and 15.0 atomic % or less, a P content of 0.001 atomic % or more and 0.500 atomic % or less, with the balance consisting of Fe and impurities, and has an amorphous structure. Further, in this metallic glass powder, the difference ΔTx between the crystallization temperature Tx and the glass transition temperature Tg is 50°C or more and 80°C or less.

[0013] According to this configuration, a metallic glass powder that has high hardness and high corrosion resistance and enables production of a non-magnetic additively manufactured body can be obtained. Then, by subjecting such metallic glass powder to powder bed fusion additive manufacturing, an additively manufactured body that is less prone to scratches, corrosion and the like and has the feature of being non-magnetic can be produced.

[0014] 1.1. Composition Cr (chromium) is an element that mainly contributes to corrosion resistance, higher hardness, non-magnetization and the like of the metallic glass powder.

[0015] The Cr content is 10.0 atomic % or more and 20.0 atomic % or less, preferably 12.0 atomic % or more and 18.0 atomic % or less, and more preferably 15.0 atomic % or more and 17.0 atomic % or less.

[0016] If the Cr content is lower than the aforementioned lower limit, the corrosion resistance of the metallic glass powder decreases, and sufficient non-magnetization cannot be achieved. If the Cr content exceeds the aforementioned upper limit, the amorphous forming ability decreases, and sufficient higher hardness cannot be achieved.

[0017] Mo (molybdenum), when added together with Cr, is an element that contributes to the corrosion resistance, increased hardness, and non-magnetic properties of metallic glass powder.

[0018] The Mo content is 10.0 atomic% or more and 20.0 atomic% or less, preferably 12.0 atomic% or more and 18.0 atomic% or less, and more preferably 15.0 atomic% or more and 17.0 atomic% or less.

[0019] If the Mo content falls below the lower limit, the corrosion resistance of the metallic glass powder decreases, and sufficient non-magnetic properties cannot be achieved. If the Cr content exceeds the upper limit, the amorphous formation ability decreases, and sufficient hardness cannot be achieved.

[0020] Carbon (C), when added together with boron (B), is an element that enhances the amorphous formation ability of metallic glass powder.

[0021] The C content is 10.0 atomic% or more and 20.0 atomic% or less, preferably 12.0 atomic% or more and 18.0 atomic% or less, and more preferably 14.0 atomic% or more and 16.0 atomic% or less.

[0022] The content of B is 5.0 atomic% or more and 15.0 atomic% or less, preferably 7.0 atomic% or more and 13.0 atomic% or less, and more preferably 9.0 atomic% or more and 11.0 atomic% or less.

[0023] If the content of C and B falls below the aforementioned lower limit, it becomes difficult to amorphous and demagneticize the metallic glass powder. If the content of C and B exceeds the aforementioned upper limit, the corrosion resistance of the metallic glass powder decreases.

[0024] Phosphorus (P), when used in combination with C and B, is an element that enhances the amorphous formation ability of metallic glass powders.

[0025] The P content is 0.001 atomic% or more and 0.500 atomic% or less, preferably 0.003 atomic% or more and 0.300 atomic% or less, and more preferably 0.005 atomic% or more and 0.100 atomic% or less.

[0026] If the P content falls below the lower limit, the amorphous formation ability decreases, making it difficult to form amorphous metal in the metal glass powder depending on the manufacturing conditions, such as the cooling rate from the molten metal during production. This results in insufficient corrosion resistance and hardness of the metal glass powder. If the P content exceeds the upper limit, the corrosion resistance of the metal glass powder decreases.

[0027] The metallic glass powder according to this embodiment may contain silicon (Si). Si is an element that enhances the fluidity of the molten metal obtained by melting the raw materials of the metallic glass powder. Si is also an element that contributes to increasing the hardness of the metallic glass powder.

[0028] The Si content is preferably more than 0 atomic% and 1.2 atomic% or less, more preferably 0.1 atomic% to 1.2 atomic%, even more preferably 0.3 atomic% to 1.1 atomic%, and particularly preferably 0.5 atomic% to 1.0 atomic%. If the Si content is within the above range, the meltability of the raw material can be increased, and the manufacturing efficiency of the metallic glass powder can be improved. In addition, a metallic glass powder with high hardness can be obtained.

[0029] If the Si content falls below the lower limit, the meltability of the raw material may decrease, potentially reducing the manufacturing efficiency of the metallic glass powder. Furthermore, the hardness of the metallic glass powder may decrease. If the Si content exceeds the upper limit, the amorphous-forming ability of the metallic glass powder may decrease. Additionally, additively manufactured bodies produced using the metallic glass powder may become brittle.

[0030] In the metallic glass powder according to the embodiment, the remainder other than the above-mentioned components consists of Fe (iron) and impurities.

[0031] Of these, Fe is the main component of metallic glass powder and is the element with the highest atomic ratio of content.

[0032] Impurities are unavoidable impurities that are present in the raw materials or introduced from the manufacturing equipment. The elements that constitute impurities are any elements other than those listed above. The total impurity content is preferably 1.0 mass% or less, more preferably 0.2 mass% or less, and even more preferably 0.1 mass% or less. Furthermore, the content of individual impurity elements is preferably 0.2 mass% or less, more preferably 0.1 mass% or less, and even more preferably 0.05 mass% or less. Within this range, the impurities are less likely to impair the effects, so their presence is acceptable.

[0033] The oxygen content of the metallic glass powder is preferably 50 ppm to 1000 ppm, more preferably 70 ppm to 500 ppm, and even more preferably 100 ppm to 300 ppm. If the oxygen content is within the above range, the occurrence of melting defects originating from metal oxides can be suppressed. As a result, metallic glass powder can be obtained that enables the manufacture of additively fabricated bodies with increased hardness, corrosion resistance, and strength.

[0034] If the oxygen content of the metallic glass powder falls below the lower limit, the difficulty of manufacturing the metallic glass powder increases, and the storage stability of the metallic glass powder may decrease. If the oxygen content of the metallic glass powder exceeds the upper limit, the occurrence of melting defects in the metallic glass powder may increase.

[0035] The nitrogen content of the metallic glass powder is preferably 50 ppm to 1000 ppm, more preferably 70 ppm to 500 ppm, and even more preferably 100 ppm to 400 ppm. If the nitrogen content is within the above range, the occurrence of melting defects originating from metal nitrides can be suppressed. As a result, metallic glass powder can be obtained that enables the manufacture of additively fabricated bodies with increased hardness, corrosion resistance, and strength.

[0036] If the nitrogen content of the metallic glass powder falls below the lower limit, the difficulty of manufacturing the metallic glass powder increases. If the nitrogen content of the metallic glass powder exceeds the upper limit, there is a risk of an increase in melting defects in the metallic glass powder.

[0037] The composition of metallic glass powder is determined by the following analytical methods. Examples of analytical methods include atomic absorption spectrometry for iron and steel as specified in JIS G 1257:2000, ICP emission spectrometry for iron and steel as specified in JIS G 1258:2007, spark discharge emission spectrometry for iron and steel as specified in JIS G 1253:2002, X-ray fluorescence spectrometry for iron and steel as specified in JIS G 1256:1997, and gravimetric titration-absorbance spectrophotometric methods as specified in JIS G 1211 to G 1237.

[0038] Specifically, examples include solid-state emission spectrometers manufactured by SPECTRO, particularly spark discharge emission spectrometers, model: SPECTROLAB, type: LAVMB08A, and the ICP instrument CIROS120 manufactured by Rigaku Corporation.

[0039] For the identification of carbon (C) and sulfur (S), the oxygen-stream combustion (high-frequency induction heating furnace combustion)-infrared absorption method specified in JIS G 1211:2011 is also used. Specifically, the LECO CS-200 carbon-sulfur analyzer is used.

[0040] When determining the presence of nitrogen (N) and oxygen (O), the methods for determining nitrogen in iron and steel specified in JIS G 1228:1997 and the general rules for determining oxygen in metallic materials specified in JIS Z 2613:2006 are also used. Specifically, the LECO TC-300 / EF-300 oxygen / nitrogen analyzer is an example.

[0041] 1.2.Metal structure The metallic glass powder according to this embodiment has an amorphous structure. The presence of an amorphous structure in metallic glass powder can be confirmed from the spectrum obtained by X-ray diffraction. Specifically, if there are no sharp diffraction peaks in the spectrum and a halo peak characteristic of an amorphous structure is observed, it can be said that the powder has an amorphous structure.

[0042] Due to its amorphous structure, the metallic glass powder particles contain virtually no grain boundaries, resulting in excellent hardness, corrosion resistance, and toughness. Therefore, by using metallic glass powder in powder bed fusion additive manufacturing, it is possible to produce additively manufactured bodies that are resistant to scratches and corrosion, and that are non-magnetic.

[0043] 1.3. Supercooled liquid region A differential scanning calorimetry (DSC) curve can be obtained from the metallic glass powder according to the embodiment by performing DSC measurements using a DSC meter. The glass transition temperature Tg and crystallization temperature Tx of the metallic glass powder can be determined from the DSC curve. The temperature range for DSC measurement is from room temperature to 750.0°C. The sample weight is 10 mg, and the heating rate is 0.67°C / second.

[0044] Figure 1 shows an example of a DSC curve obtained for a metallic glass powder according to the embodiment. In Figure 1, the horizontal axis represents temperature and the vertical axis represents heat flow. When the glass transition temperature Tg is determined from the DSC curve shown in Figure 1 using the tangent method, it is found to be 618.9°C. When the glass transition temperature Tg can be determined in this way using the tangent method, it can be said that the metallic glass powder has an amorphous structure.

[0045] Furthermore, the crystallization temperature Tx of the DSC curve shown in Figure 1 is determined to be 684.0°C using the tangent method.

[0046] The difference between the crystallization temperature Tx and the glass transition temperature Tg obtained as described above is called the "supercooled liquid region ΔTx". The supercooled liquid region ΔTx is a quantitative indicator of the amorphous formation ability of the metallic glass powder; the larger the value, the higher the amorphous formation ability. In the example shown in Figure 1, the supercooled liquid region ΔTx is 65.1°C.

[0047] In the metallic glass powder according to this embodiment, the supercooled liquid region ΔTx is 50°C or more and 80°C or less, preferably 53°C or more and 78°C or less, and more preferably 56°C or more and 75°C or less.

[0048] If the supercooled liquid region ΔTx falls below the lower limit, the amorphous formation ability of the metallic glass powder decreases, resulting in either no amorphous structure being formed or a decrease in the packing density of the amorphous structure. If the supercooled liquid region ΔTx exceeds the upper limit, it becomes difficult to stably manufacture the metallic glass powder.

[0049] 1.4.Particle size In the volume-based cumulative particle size distribution of metallic glass powder obtained using a laser diffraction particle size distribution analyzer, the particle size at which the cumulative frequency from the smallest diameter side reaches 50% is defined as D50 (average particle size).

[0050] The particle size D50 of the metallic glass powder is preferably 5.0 μm to 40.0 μm, more preferably 10.0 μm to 35.0 μm, and even more preferably 20.0 μm to 30.0 μm. If the particle size D50 of the metallic glass powder is within the above range, the fluidity and packing properties of the metallic glass powder can be improved. This improves the packing properties of the powder bed, and ultimately, a high-density additively manufactured body can be formed. As a result, a high-density additively manufactured body with increased hardness, corrosion resistance, and strength can be obtained.

[0051] If the particle size D50 of the metallic glass powder falls below the lower limit, the particle size becomes too small, which may lead to a decrease in the fluidity and packing ability of the metallic glass powder due to aggregation. If the particle size D50 exceeds the upper limit, the particle size becomes too large, which may lead to a decrease in amorphous formation ability or a decrease in packing ability.

[0052] In the volume-based cumulative particle size distribution of metallic glass powder obtained using a laser diffraction particle size distribution analyzer, the particle size at which the cumulative frequency from the smallest diameter side reaches 10% is defined as D10, and the particle size at which it reaches 90% is defined as D90.

[0053] The particle size ratio D10 / D90 of the metallic glass powder indicates the extent of the particle size distribution. The particle size ratio D10 / D90 of the metallic glass powder is preferably 0.15 to 0.32, more preferably 0.17 to 0.30, and even more preferably 0.20 to 0.28. When the particle size ratio D10 / D90 is within this range, the fluidity and packing properties of the metallic glass powder are particularly good.

[0054] If the particle size ratio D10 / D90 of the metallic glass powder falls below the lower limit, fluidity may decrease. If the particle size ratio D10 / D90 of the metallic glass powder exceeds the upper limit, packing performance may decrease.

[0055] 1.5. Tap Density The tap density of the metallic glass powder according to this embodiment is 4.3 g / cm³. 3 More than 5.5g / cm 3 Preferably, it is 4.5 g / cm³ 3 More than 5.3g / cm 3 It is more preferable to be 4.8 g / cm³ 3 More than 5.2g / cm 3 It is even more preferable that the tap density is within the above range, which improves the fluidity and packing properties of the metallic glass powder. This improves the packing properties of the powder bed, ultimately enabling the formation of a high-density additively manufactured body.

[0056] The tap density of metallic glass powder is measured using the Powder Tester® PT-X powder property evaluation device manufactured by Hosokawa Micron Corporation. Prior to measuring the tap density, it is preferable to leave the metallic glass powder to be measured in an environment of 25°C and 50% relative humidity for at least one hour.

[0057] 1.6. Mean Circularity The average circularity of the metallic glass powder according to this embodiment is preferably 0.80 to 0.95, more preferably 0.82 to 0.94, and even more preferably 0.84 to 0.93. If the average circularity is within the above range, the fluidity and packing properties of the metallic glass powder will be good. This improves the packing properties of the powder bed, and as a result, a high-density additively manufactured body can be formed.

[0058] The average circularity of metallic glass powder is obtained as follows: First, an image (secondary electron image) of the metallic glass powder is captured using a scanning electron microscope (SEM). Next, the obtained image is loaded into image processing software. For example, image processing software such as "Mac-View," an image analysis-based particle size distribution measurement software manufactured by Mountec Co., Ltd. is used. The imaging magnification is adjusted so that 50 to 100 particles are captured in each image. Then, multiple images are acquired so that a total of 300 or more particle images are obtained.

[0059] Next, the circularity of more than 300 particle images is calculated using software. When the circularity is e, the area of ​​the particle image is S, and the perimeter of the particle image is L, the circularity e can be calculated using the following formula. e = 4πS / L 2

[0060] Next, the average value of the calculated circularity is determined. The resulting average value represents the average circularity of the metallic glass powder.

[0061] 1.7.Hardness In an additively manufactured body produced by a predetermined method using the metallic glass powder according to the embodiment, the Vickers hardness of the cross-section is preferably 1000 to 2000, and more preferably 1200 to 1500. If the Vickers hardness is within the above range, an additively manufactured body that is resistant to scratches, dents, and the like can be realized.

[0062] The method for measuring hardness is as follows: First, the metallic glass powder according to the embodiment is subjected to additive manufacturing using a powder bed fusion method to produce an additively manufactured sample that is cylindrical in shape with an outer diameter of 25 mm, an inner diameter of 15 mm, and a length of 20 mm. Next, the fabricated additively manufactured sample is cut along the plane through which the cylinder's axis passes. Next, the cut surface is mirror-polished, and then its hardness is measured using a micro-Vickers hardness tester. The measurement position is the center of the rectangular cut surface. The indentation load during measurement is set to 0.98 N.

[0063] 1.8.Nonmagnetic properties In the embodiment, the metallic glass powder is filled into an annular resin case, and then an annular solenoid coil is wound around it to form a sample for the powder. Alternatively, an annular solenoid coil is wound around an empty resin case to form an air-core sample. When the inductance of the sample for the powder is L1 and the inductance of the air-core sample is L0, the ratio of inductance L1 to inductance L0, L1 / L0, is preferably 1.000 or more and 1.020 or less, and more preferably 1.000 or more and 1.010 or less.

[0064] With this configuration, a metallic glass powder with a sufficiently low relative permeability and good non-magnetic properties can be obtained.

[0065] The inductances L0 and L1 are obtained as follows: First, the metallic glass powder is filled into the resin case. During filling, the resin case is vibrated sufficiently until the volume of the metallic glass powder no longer changes. The resin case is an annular case with an outer diameter of 31.30 mm, an inner diameter of 19.14 mm, a height of 6.98 mm, and a plate thickness of 1.00 mm.

[0066] Next, a resin case filled with metallic glass powder is wrapped seven times with a 0.7 mm diameter copper wire to form an annular solenoid coil, thereby creating a sample for the powder.

[0067] Next, the inductance of the prepared powder sample at a frequency of 1 MHz is measured using an impedance analyzer. The measurement result is denoted as the inductance L1 [μH]. For example, a Keysight Technologies 4294A impedance analyzer is used. The magnetic field strength during measurement is set to 5 [mOe].

[0068] Next, after removing the metallic glass powder from the resin case, a copper wire with a diameter of 0.7 mm is wound around the resin case seven times to form an annular solenoid coil, and an air-core specimen is prepared.

[0069] Next, the inductance of the fabricated air-core specimen is measured at a frequency of 1 MHz in the same manner. The measurement result is defined as the inductance L0 [μH].

[0070] 2. Method for producing metallic glass powder Next, we will describe an example of a method for producing metallic glass powder.

[0071] Metallic glass powder can be produced by any manufacturing method, but for example, it can be produced by atomization. In atomization, molten metal is allowed to flow from a crucible and collide with a fluid such as a liquid or gas that is ejected at high speed. This increases the cooling rate and makes it possible to produce metallic glass powder with a good amorphous structure.

[0072] Atomization methods include water atomization, gas atomization, and rotary water flow atomization, depending on the type of coolant and the configuration of the equipment.

[0073] The flow rate of molten metal varies depending on the size of the apparatus, but is preferably between 1.0 kg / min and 20.0 kg / min, and more preferably between 2.0 kg / min and 10.0 kg / min. This allows for the optimization of the amount of molten metal flowing in a given time, enabling the efficient production of metallic glass powder with a good amorphous structure, sufficient spheroidization, and an optimized particle size distribution.

[0074] The temperature of the molten metal in the crucible (casting temperature) is preferably set to Tm+100°C to Tm+350°C, more preferably to Tm+180°C to Tm+320°C, and even more preferably to Tm+250°C to Tm+300°C, relative to the melting point Tm[°C] of the constituent material of the metallic glass powder. This allows for a longer period of time in which the molten metal exists when it is atomized and solidified by various atomization methods. As a result, metallic glass powder with high average circularity, good fluidity and packing properties can be produced.

[0075] Furthermore, in various atomization methods, the outer diameter of the narrow stream when molten metal is flowed down is not particularly limited, but is preferably 3.0 mm or less, more preferably 0.3 mm to 2.0 mm, and even more preferably 0.5 mm to 1.5 mm. This makes it easier to apply the fluid uniformly to the molten metal, thereby ensuring a sufficient cooling rate and optimizing spheroidization and particle size distribution.

[0076] Furthermore, the manufactured metallic glass powder may be classified as needed. Examples of classification methods include dry classification such as sieving, inertial classification, and centrifugal classification, and wet classification such as sedimentation classification.

[0077] Furthermore, the particle surface of the manufactured metallic glass powder may be subjected to a surface treatment. Examples of surface treatments include coupling agent treatment.

[0078] 3. Additive-type fabricated body The additively manufactured body according to the embodiment is produced by subjecting the metallic glass powder according to the embodiment to a powder bed fusion additive manufacturing method.

[0079] Powder bed fusion additive manufacturing has, for example, the following steps: First, a powder bed is formed using metallic glass powder. While the powder bed may be formed using metallic glass powder alone, it may also be formed using a mixed powder containing additives to the metallic glass powder.

[0080] Examples of additives include non-metallic powders, preservatives, antioxidants, coupling agents, and energy absorption enhancers.

[0081] Among these, non-metallic powders include, for example, inorganic powders such as glass powder and ceramic powder. Examples of constituent materials for ceramic powders include oxide-based ceramics such as silicon oxide, magnesium oxide, calcium oxide, aluminum oxide, titanium oxide, zirconium oxide, boron oxide, and yttrium oxide, and non-oxide-based ceramics such as silicon nitride, aluminum nitride, boron nitride, titanium nitride, silicon carbide, boron carbide, titanium carbide, and tungsten carbide.

[0082] In forming the powder bed, for example, a powder bed of a predetermined thickness is formed by leveling the metallic glass powder using a recoater.

[0083] Next, electromagnetic radiation is irradiated onto the powder bed to melt the irradiated metallic glass powder. This forms a molten metallic glass powder in the target area.

[0084] Next, a new powder bed is formed to cover the powder bed in which the molten metallic glass powder has been formed. Then, electromagnetic radiation is irradiated again to form molten metallic glass powder in the target area.

[0085] By repeating the above process, a three-dimensional additively fabricated body is ultimately formed. Laser light is preferably used as the electromagnetic radiation. Examples of laser light include carbon dioxide lasers, YAG lasers, excimer lasers, He-Cd lasers, and semiconductor-pumped solid-state lasers.

[0086] The resulting additively manufactured bodies have high hardness and corrosion resistance, as well as being non-magnetic. For this reason, additively manufactured bodies according to this embodiment can be used in a wide range of applications, such as components for electronic devices, electronic parts, jewelry, and ornaments.

[0087] Furthermore, the resulting additively fabricated body has the advantage of having a lower coefficient of thermal expansion compared to other non-magnetic metal materials. Therefore, it is possible to create parts that are non-magnetic and exhibit minimal dimensional changes due to temperature fluctuations.

[0088] 4.Electronic equipment The electronic device according to the embodiment includes the additively manufactured body according to the embodiment described above. Examples of such electronic devices include portable electronic devices and stationary electronic devices. By using the additively manufactured body for the casing of a portable electronic device, it is possible to realize a portable electronic device that is less susceptible to scratches and corrosion. Furthermore, since the additively manufactured body is nonmagnetic, it can suppress the influence of magnetic fields generated by electromagnetic waves on electronic circuits. This can suppress performance degradation of electronic circuits.

[0089] Examples of portable electronic devices include mobile phones, smartphones, portable music players, tablet devices, notebook computers, smartwatches, wearable devices, and portable medical devices.

[0090] 5. Effects of the Embodiment As described above, the metallic glass powder according to the embodiment is used in powder bed fusion additive manufacturing. This metallic glass powder has a Cr content of 10.0 atomic% to 20.0 atomic%, a Mo content of 10.0 atomic% to 20.0 atomic%, a C content of 10.0 atomic% to 20.0 atomic%, a B content of 5.0 atomic% to 15.0 atomic%, and a P content of 0.001 atomic% to 0.500 atomic%, with the remainder being Fe and impurities. Furthermore, the metallic glass powder according to the embodiment has an amorphous structure, and the difference between the crystallization temperature Tx and the glass transition temperature Tg is 50°C to 80°C.

[0091] This configuration yields a metallic glass powder capable of producing additively manufactured bodies with high hardness and corrosion resistance, as well as being non-magnetic. By using this metallic glass powder in powder bed fusion additive manufacturing, additively manufactured bodies that are resistant to scratches and corrosion, and possess the characteristics of being non-magnetic, can be produced.

[0092] The metallic glass powder according to the embodiment preferably has a Si content of 0.1 atomic% or more and 1.2 atomic% or less.

[0093] This configuration allows for increased melting properties of the raw materials, thereby improving the efficiency of metallic glass powder production. Furthermore, it enables the production of high-hardness metallic glass powder.

[0094] In the embodiment of the metallic glass powder, when used in additive manufacturing by powder bed fusion and a cylindrical additive manufacturing sample with an outer diameter of 25 mm, an inner diameter of 15 mm, and a length of 20 mm is produced, it is preferable that the Vickers hardness of the cross-section of the additive manufacturing sample is 1000 or more and 2000 or less.

[0095] This configuration yields a metallic glass powder that can be used to manufacture additively fabricated bodies that are resistant to scratches and dents.

[0096] In the metallic glass powder according to the embodiment, after being filled into an annular resin case having an outer diameter of 31.30 mm, an inner diameter of 19.14 mm, and a height of 6.98 mm, an annular solenoid coil is wound around the resin case to produce a test specimen for powder, and an annular solenoid coil is wound around an empty resin case to produce an air-core test specimen. When the inductance of the test specimen for powder is denoted as L1 and the inductance of the air-core test specimen is denoted as L0, the ratio L1 / L0 of the inductance L1 to the inductance L0 is preferably 1.000 or more and 1.020 or less.

[0097] According to this configuration, a metallic glass powder having a sufficiently low relative magnetic permeability and excellent non-magnetic properties can be obtained.

[0098] In the metallic glass powder according to the embodiment, the average particle diameter is preferably 5.0 µm or more and 40.0 µm or less. According to this configuration, a metallic glass powder having high fluidity and high fillability can be obtained.

[0099] In the metallic glass powder according to the embodiment, the tap density is 4.3 g / cm 3 or more and 5.5 g / cm 3 or less, which is preferable. According to this configuration, a metallic glass powder having high fluidity and high fillability can be obtained.

[0100] In the metallic glass powder according to the embodiment, the average circularity is preferably 0.80 or more and 0.95 or less. According to this configuration, a metallic glass powder having high fluidity and high fillability can be obtained.

[0101] The additive-manufactured body according to the embodiment is obtained by subjecting the metallic glass powder according to the aforementioned embodiment to powder bed fusion additive manufacturing.

[0102] According to this configuration, a non-magnetic additive-manufactured body having high hardness and high corrosion resistance can be obtained.

[0103] The electronic device according to this embodiment includes the additively manufactured body according to the above-described embodiment. This configuration makes it possible to create portable electronic devices that are less susceptible to scratches and corrosion, for example. Furthermore, because the additively manufactured body is non-magnetic, it can suppress the influence of magnetic fields generated by electromagnetic waves on electronic circuits. This helps to prevent performance degradation of electronic circuits.

[0104] Although the metallic glass powder, additive manufactured body, and electronic device according to the present invention have been described above based on the illustrated embodiments, the present invention is not limited thereto. For example, the metallic glass powder, additive manufactured body, and electronic device according to the present invention may have any configuration added to the above embodiments. [Examples]

[0105] Next, specific embodiments of the present invention will be described. 6. Manufacturing of metallic glass powder Metallic glass powders (Samples No. 1-18) and metal powders (Samples No. 19-21) were prepared by classifying powders produced using the rotary water atomization method. The various conditions used in the rotary water atomization method are as follows.

[0106] • Outer diameter of the molten metal stream: 3.0 mm • Molten metal flow rate: 5.0 kg / min • Casting temperature: Tm + 270℃

[0107] The composition of the metallic glass powder and metal powder for each sample No. is shown in Tables 1 (Figure 2) to 4 (Figure 5). Figure 2 is Table 1 showing the composition of the metallic glass powder. Figure 3 is Table 2 showing the composition of the metallic glass powder or metal powder. Figure 4 is Table 3 showing the properties of the metallic glass powder and the evaluation results of the additively manufactured body. Figure 5 is Table 4 showing the properties of the metallic glass powder or metal powder and the evaluation results of the additively manufactured body.

[0108] Furthermore, the composition of the metallic glass powder or metal powder and the supercooled liquid region ΔTx of the metallic glass powder are shown in Tables 1 and 2.

[0109] Furthermore, the properties of the metallic glass powder or metal powder, including particle size D10, D50, D90, particle size ratio D10 / D90, oxygen content, nitrogen content, tap density, and average roundness, are shown in Tables 3 and 4.

[0110] Furthermore, in Tables 2 to 4, among the powders of each sample number, those corresponding to the present invention are designated as "Examples," and those not corresponding to the present invention are designated as "Comparative Examples."

[0111] 7. Evaluation of additively manufactured objects Each sample No. powder was subjected to additive manufacturing using powder bed fusion to produce evaluation additively manufactured cylindrical bodies with an outer diameter of 25 mm, an inner diameter of 15 mm, and a length of 20 mm. For the additive manufacturing process, a mixed powder was used, consisting of 0.02 parts by mass of silica powder to 100 parts by mass of each sample No. powder. The particle size D50 of the silica powder was 10 nm.

[0112] Next, the following evaluations were performed on the additively fabricated objects created for evaluation. 7.1.Metal structure The fabricated additively manufactured structures for evaluation were subjected to crystal structure analysis by X-ray diffraction. Based on the obtained X-ray diffraction spectra, the presence or absence of an amorphous structure was evaluated. The evaluation results are shown in Tables 3 and 4, with "A" indicating the presence of an amorphous structure and "C" indicating the absence of an amorphous structure.

[0113] 7.2.Hardness The Vickers hardness of the fabricated additively manufactured objects was measured using the method described above. The hardness of the additively manufactured objects was then evaluated against the following evaluation criteria based on the measurement results. The evaluation results are shown in Tables 3 and 4.

[0114] A: The Vickers hardness is between 1200 and 1500. B: The Vickers hardness is between 1000 and 1200 or between 1500 and 2000. C: Vickers hardness is less than 1000 or greater than 2000.

[0115] 7.3. Corrosion resistance The additively manufactured objects prepared for evaluation were subjected to a neutral salt spray test as specified in JIS Z 2371:2015. A 5% neutral salt solution was used as the spray solution, and the test was conducted at 35°C for 48 hours. The corrosion resistance of the additively manufactured objects was then evaluated against the following evaluation criteria. The evaluation results are shown in Tables 3 and 4.

[0116] A: There is almost no change in appearance. B: A slight change in appearance is observed. C: Significant changes in appearance

[0117] 7.4.Nonmagnetic properties For the powder used to fabricate the additively manufactured bodies for evaluation, the inductance ratio L1 / L0, which represents the non-magnetic properties, was calculated using the method described above. The non-magnetic properties of the additively manufactured bodies were then evaluated by comparing the calculation results against the following evaluation criteria. The evaluation results are shown in Tables 3 and 4.

[0118] A: The inductance ratio L1 / L0 is between 1.000 and 1.010. B: The inductance ratio L1 / L0 is greater than 1.010 and less than or equal to 1.020. C: The inductance ratio L1 / L0 is greater than 1.020.

[0119] 7.5. Discussion of the Evaluation Results As shown in Tables 3 and 4, it was confirmed that additively manufactured bodies with high hardness and corrosion resistance can be produced by using the metallic glass powders of each example. Furthermore, it was confirmed that additively manufactured bodies with non-magnetic properties equivalent to those of non-magnetic stainless steels such as SUS304 and SUS316L can be produced by using the metallic glass powders of each example. [Explanation of Symbols]

[0120] Tm... Melting point, Tx... Crystallization temperature, ΔTx... Supercooled liquid region

Claims

1. A metallic glass powder used in powder bed fusion additive manufacturing, The Cr content is 10.0 atomic% or more and 20.0 atomic% or less. The Mo content is 10.0 atomic% or more and 20.0 atomic% or less. The C content is 10.0 atomic% or more and 20.0 atomic% or less. The content of B is 5.0 atomic% or more and 15.0 atomic% or less. The P content is 0.001 atomic% or more and 0.500 atomic% or less. The remainder consists of Fe and impurities. It has an amorphous structure, A metallic glass powder characterized by having a difference between its crystallization temperature Tx and its glass transition temperature Tg of 50°C or more and 80°C or less.

2. The metallic glass powder according to claim 1, wherein the Si content is 0.1 atomic% or more and 1.2 atomic% or less.

3. When a cylindrical additive manufacturing sample with an outer diameter of 25 mm, an inner diameter of 15 mm, and a length of 20 mm is produced using powder bed fusion additive manufacturing, The metallic glass powder according to claim 1, wherein the Vickers hardness of the cross-section of the additively manufactured sample is 1000 or more and 2000 or less.

4. After filling a resin case forming an annular shape with an outer diameter of 31.30 mm, an inner diameter of 19.14 mm, a height of 6.98 mm, and a plate thickness of 1.00 mm, a sample for powder is prepared by winding an annular solenoid coil around the resin case, and an air-core sample is prepared by winding the annular solenoid coil around an empty resin case. When the inductance of the sample for powder is L1 and the inductance of the air-core sample is L0, The metallic glass powder according to claim 1, wherein the ratio of inductance L1 to inductance L0, L1 / L0, is 1.000 or more and 1.020 or less.

5. The metallic glass powder according to claim 1, wherein the average particle size is 5.0 μm or more and 40.0 μm or less.

6. Tap density is 4.3 g / cm³ 3 5.5g / cm or more 3 The metallic glass powder according to claim 1, wherein the following applies:

7. The metallic glass powder according to claim 1, wherein the average circularity is 0.80 or more and 0.95 or less.

8. A laminated body characterized in that the metallic glass powder described in any one of claims 1 to 6 is subjected to additive manufacturing by powder bed fusion bonding.

9. An electronic device characterized by comprising an additively manufactured body as described in claim 8.

Citation Information

Patent Citations

  • Method for molding three-dimensional product

    JP2002249804A

Cited By

  • Metallic glass powder, additively manufactured body, and electronic device

    EP4799746A1